PENDIDIKAN KARAKTER SISWA BERBASIS AL-QUR’AN PADA ANAK USIA DINI DI PAUD-TPQ MIFTAHUL HUDA TEMANGGUNG - Chusna Amalia Zulfa; Lilik Rohmat Nurcholisho; Nurul Mubin (Ta'dib (Jurnal Ilmiah Pendidikan dan Peradaban Islam), 2020)
This research speaks about the character-building process conducted by early childhood teachers to expose the student to the qur'anic way of life at PAUD-TPQ Miftahul Huda. This descriptive-qualitative research has been done in PAUD-TPQ Miftahul Huda, Temanggung, using the study case model as the primary research approach. The data collection methods are observation, interview, and documentation methods. Informants were selected using a series of processes of data collection, reduction, presentation, and verification of data and analysis during the process. The credibility of the data will be checked by observing the reference adequacy procedure. Meanwhile, dependability and confirmability are achieved through auditing by supervisors. The results of the study show that: To make a nation with a strong character, the government issued Presidential Regulation (Perpres) Number: 87 of 2017 concerning Strengthening Character Education; (2) Building the student character must start in an early ages, because the growth of brain tissue cells at the age of 0-4 years reaches 50% (3) The learning method that is widely used for early childhood is the method of playing and learning; (4) The building of children's character in schools begins by applying a modeling, exemplary / uswah hasanah approach, which means using and familiarizing the school environment to uphold moral values and good characters; (5) The role of parents will determine the quality of children's attitude in the future; (6) Surveillance of games preference for the children needs to be carried out, so that the games that children choose to play have a good impact on them such as traditional games that can improve children's character, knowledge, and their social skills 7) The mistakes in choosing the type of game in children, can potentially have a harmful impact to them, for example an addicted-online gamers can cause a child having double personality and tend to disengage with the social environment